Synthesis,characterization, acetylcholinesterase inhibition, molecular modeling and antioxidant activities of some novel schiff bases derived from 1-(2-ketoiminoethyl)piperazines - Salga, S.M.; Hadi, A.H.A.; Sukumaran, S.D.; Buckle, M.J.C.; Wai, L.K.; Abdelwahab, S.I.; Abdullah, M.A.; Ali, Hapipah Mohd (2011)
Some novel Schiff bases derived from 1-(2-ketoiminoethyl)piperazines were synthesized and characterized by mass spectroscopy, FTIR, UV-Visible, (1)H and (13)C-NMR. The compounds were tested for inhibitory activities on human acetylcholinesterase (hAChE), antioxidant activities, acute oral toxicity and further studied by molecular modeling techniques. The study identified the compound (DHP) to have the highest activity among the series in hAChE inhibition and DPPH assay while the compound LP revealed the highest activity in the FRAP assay. The hAChE inhibitory activity of DHP is comparable with that of propidium, a known AChE inhibitor. This high activity of DHP was checked by molecular modeling which showed that DHP could not be considered as a bivalent ligand due to its incapability to occupy the esteratic site (ES) region of the 3D crystal structure of hAChE. The antioxidant study unveiled varying results in 1,1-diphenyl-1-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) assays. This indicates mechanistic variations of the compounds in the two assays. The potential therapeutic applications and safety of these compounds were suggested for use as human acetylcholinesterase inhibitors and antioxidants.